Play as a Factor of Harmonious and Disharmonious Development in Childhood - S.A. Voskresenskaya; G.V. Kozlovskaya; M.V. Ivanov; M.A. Kalinina (Moscow State University of Psychology and Education, 2021)
The article discusses the problems of the development of play activity, as a reflection of harmonious and disharmonious mental development, starting from an early age. 4030 preschool children (2720 boys and 1310 girls) were examined. For the long-term observation, 150 people (92 boys and 58 girls) were selected. Methods: clinical-psychopathological, neurological, psychological, using the concept of leading activity, focused on the "zone of proximal development". The article analyzes the role of toys as material objects used by children of different ages and clinical conditions, in the structure of which disorders of the mental state and play activity were found. The clinical picture of mental disorders was determined by disorders of the neurosis-like, affective level in combination with individual schizotypal stigmas, and behavioral disorders within the autism spectrum disorders. Conclusions are made about the possibility of an adverse effect of certain forms of play and play objects on the mental state and development of schizo- typal disorders and autism spectrum disorders.